2020
DOI: 10.1101/2020.04.30.070359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanochemical control of epidermal stem cell divisions by B-plexins

Abstract: The precise spatiotemporal control of cell proliferation is key to the morphogenesis of epithelial tissues. Epithelial cell divisions lead to tissue crowding and local changes in force distribution, which in turn suppress the rate of cell divisions. However, the molecular mechanisms underlying this mechanical feedback are largely unclear. Here, we identify a critical requirement of B-plexin transmembrane receptors in the response to crowding-induced mechanical forces during embryonic skin development. Epiderma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For example, laminar and oscillatory shear can regulate PLXND1 configuration to influence cellular mechanoresponses during atherosclerosis. During development, cell-cell contact may also act through PLXNB to control YAP/TAZ subcellular location, but the exact effects of plexins on YAP activity are not entirely consistent among different studies (39)(40)(41). We observed that overexpression of PLXNA1 or PLXND1 did not counteract YAP phosphorylation by high cell density, whereas expression of the positive control lysophosphatidic acid receptor LPAR1 decreased YAP phosphorylation (Fig.…”
Section: Oscillatory Shear Stress Blocks Sema3a-induced Yap/taz Inact...mentioning
confidence: 66%
See 1 more Smart Citation
“…For example, laminar and oscillatory shear can regulate PLXND1 configuration to influence cellular mechanoresponses during atherosclerosis. During development, cell-cell contact may also act through PLXNB to control YAP/TAZ subcellular location, but the exact effects of plexins on YAP activity are not entirely consistent among different studies (39)(40)(41). We observed that overexpression of PLXNA1 or PLXND1 did not counteract YAP phosphorylation by high cell density, whereas expression of the positive control lysophosphatidic acid receptor LPAR1 decreased YAP phosphorylation (Fig.…”
Section: Oscillatory Shear Stress Blocks Sema3a-induced Yap/taz Inact...mentioning
confidence: 66%
“…Mechanical cues-such as cell-cell contact, matrix stiffness, and flow shear-can regulate Hippo signaling (11,38). PLXND1 and PLXNB1/2 were reported to respond to mechanical cues to modulate cell behaviors (39)(40)(41). For example, laminar and oscillatory shear can regulate PLXND1 configuration to influence cellular mechanoresponses during atherosclerosis.…”
Section: Oscillatory Shear Stress Blocks Sema3a-induced Yap/taz Inact...mentioning
confidence: 99%
“…96,98 In summary, different mechanical cues are involved in the upstream regulation of the Hippo pathway. Although it has been found that integrin, 99 peizo 100 and plexin 101 can act as mechanical sensor proteins that transmit signals to the Hippo pathway, the comprehensive molecular mechanism by which cells sense mechanical signals and change cellular behaviours through the Hippo pathway is still unclear. The proteins in cellcell contact sites and the cytoskeleton might play critical roles in the signal transmission between mechanical cues and the Hippo pathway cascade.…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…1H-J). To further exclude the possibility of non-specific reagent activity, knockdown was performed with 2 conventional previously validated silencing RNAs against YAP (siYAP) (Dupont et al , 2011) or with the pharmacological inhibitor of YAP, Verteporfin (Ning et al , 2021; McGinn et al , 2021; Jiang et al , 2021). In agreement, both siRNA repression (S1A-B) and pharmacology inhibition (Fig.…”
Section: Resultsmentioning
confidence: 99%